2020
DOI: 10.3390/ijms21031139
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyl Cyclase-cGMP Signaling Pathway in Melanocytes: Differential Effects of Altered Gravity in Non-Metastatic and Metastatic Cells

Abstract: Human epidermal melanocytes as melanin producing skin cells represent a crucial barrier against UV-radiation and oxidative stress. It was shown that the intracellular signaling molecule cyclic guanosine-3 ,5 -monophosphate (cGMP), generated by the guanylyl cyclases (GCs), e.g., the nitric oxide (NO)-sensitive soluble GC (sGC) and the natriuretic peptide-activated particulate GC (GC-A/GC-B), plays a role in the melanocyte response to environmental stress. Importantly, cGMP is involved in NO-induced perturbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 92 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…The relationship between absorption of solar radiation and colour may explain the inclusion of putatively adaptive loci linked to genes involved in feather colour such as BCO2 , which is implicated in carotenoid‐processing in other passerines (Gazda et al, 2020; Toews et al, 2016), and the well‐studied coloration gene, Mc1r (Wolf Horrell et al, 2016). Other genes including MYRIP , RAB17 , and TRPC1 , further modify melanin synthesis, transportation, and deposition (Beaumont et al, 2011; Ivanova & Hemmersbach, 2020; Li et al, 2017; Wasmeier et al, 2008). Such results suggest that future studies should examine whether these genetic differences explain variation in plumage and feather traits across the archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between absorption of solar radiation and colour may explain the inclusion of putatively adaptive loci linked to genes involved in feather colour such as BCO2 , which is implicated in carotenoid‐processing in other passerines (Gazda et al, 2020; Toews et al, 2016), and the well‐studied coloration gene, Mc1r (Wolf Horrell et al, 2016). Other genes including MYRIP , RAB17 , and TRPC1 , further modify melanin synthesis, transportation, and deposition (Beaumont et al, 2011; Ivanova & Hemmersbach, 2020; Li et al, 2017; Wasmeier et al, 2008). Such results suggest that future studies should examine whether these genetic differences explain variation in plumage and feather traits across the archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on in vitro cell models strongly suggest that NO present in the sur-Łukasz Marek, Irena Tam, Sławomir Kurkiewicz, Anna Dzierżęga-Lęcznar rounding cellular environment can affect melanocyte physiology in a paracrine and/or autocrine manner [12]. Importantly, no such effects were observed at low NO concentrations or for short-term exposure, whereas high NO concentrations were cytotoxic and decreased cell viability [13]. It has been reported that NO induces detachment of melanocytes from the extracellular matrix, which presumably contributes to pigment cell loss in vitiligo or melanoma metastasis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 Hypergravity influences longevity in Drosophila , 11 and increases proliferation and differentiation of bone marrow stromal progenitors. 12 Moreover, several studies demonstrate that altered gravity affects signaling pathways 13 , 14 , 15 , 16 and modifies the transcriptional profile of factors not exclusively associated with stress response. 10 , 17 , 18 , 19 , 20 , 21 , 22 The understanding of the biological effects produced by altered gravity conditions is a relevant issue for spaceflight, bearing in mind that – after long‐term missions – astronauts experience a number of health problems, like atrophy of muscles, bone demineralization, cardiopulmonary, ocular and vestibular complications, and modifications in the nervous system connections.…”
Section: Introductionmentioning
confidence: 99%